Mycobacteriosis caused by Mycobacterium marinum in reared mullets: first evidence from Sardinia (Italy). Issue 3 (2nd July 2016) - Antuofermo, E; Pais, A; Polinas, M; Cubeddu, T; Righetti, M; Sanna, M A; Prearo, M
Abstract: Mycobacterium marinum is a slow‐growing non‐tuberculous mycobacterium, and it is considered the most common aetiologic agent of mycobacteriosis in wild and cultured fish. The diagnosis is principally made by histology when positive Ziehl–Neelsen stain granulomas are detected. The aim of this study was to investigate the occurrence of mycobacteriosis in extensively cultured Mugilidae of two lagoons (Cabras and San Teodoro) from Sardinia by the use of histology, microbiology, PCR and DNA sequencing. Nine of 106 mullets examined were affected by mycobacteriosis, and the spleen was the most affected organ. The histology detected higher rate (100%) of infection in spleen than the culture and PCR (75% and 62.5%, respectively). The sequencing of hsp65 gene identified M. marinum as the primary cause of mycobacteriosis in the mullets examined. Mullets affected by mycobacteriosis were mainly fished in the San Teodoro lagoon characterized by critical environmental conditions. Histology remains the most common method in detecting fish affected by mycobacteriosis, and PCR‐based methods are essential for species identification. Our finding are worthy of attention because mycobacteriosis caused by M. marinum in reared mullets was evidenced for the first time in Sardinia, suggesting that this disease may be underestimated also in other cultured fish species.